EFFECT OF MANNITOL ON ELECTROLYTES AND ITS RELATION WITH KIDNEY INJURY IN CARDIOPULMONARY BYPASS - SALEEM, M; AWAN, AH; MUSHTAQ, A (Biological and Clinical Sciences Research Journal, 2023)
The optimal composition of the priming solution used in cardiopulmonary bypass (CPB) during human cardiac surgery is still uncertain. Mannitol is a common component of CPB priming solutions, but its efficacy is debated. To clarify the effect of mannitol on CPB prime solutions, a prospective, randomized, double-blind trial was conducted on 40 patients with sound cardiac and renal functions who were undergoing coronary artery bypass grafting. The trial included two groups: one received Ringer’s acetate-based prime (n = 20), and the other received a combination of Ringer’s acetate and 200 mL mannitol as prime (n = 20). The study examined changes in renal-related parameters, electrolytes, osmolality, and acid-base balance. Interestingly, no significant differences in osmolality were observed between the Mannitol and Ringer’s acetate groups. However, the Mannitol group showed a significant decrease in sodium levels from 138.7±2.8 mmol/L at the start of anesthesia to 133.9±2.6 mmol/L after the initiation of CPB (p <0.001). Renal parameters remained consistent across groups, except for a temporary effect of mannitol on post-surgery urine output (p = 0.003). In conclusion, this study found no significant differences in osmolality between Ringer’s acetate-based prime and Mannitol-based prime in individuals with healthy cardiac and renal function. However, the addition of mannitol to the prime resulted in a significant, albeit short-term, reduction in sodium levels. These findings contribute to the ongoing discourse on optimizing CPB prime solutions, especially in cardiac surgical procedures involving mannitol inclusion.